The problematic aspects of teaching Ukrainian language for professional orientation at higher medical institutions - Соловій, Уляна (Educational Dimension, 2015)
Solovij U. V. The problematic aspects of teaching Ukrainian language for professional orientation at higher medical institutions. The current problems of teaching Ukrainian language for professional orientation at higher medical institutions both as a normative and a compulsory discipline are examined in the article; the necessity of learning it in the process of gaining the high degree of the professional training and forming the communicative, professionally orientated competence of future doctors (pharmacists) is argued.